Taxonomic study of the genus Myrmarachne of Borneo (Araneae: Salticidae) - Yamasaki, T; Abd. Hamid Ahmad (Magnolia Press, 2013)
Twenty-two species of the genus Myrmarachne are reported from Borneo in the present study. Among those, eight are new to science, M. acromegalis sp. nov., M. alticephalon sp. nov., M. brevichelicera sp. nov., M. crassembolus sp. nov., M. cyrtodens sp. nov., M. endoi sp. nov., M. lambirensis sp. nov. and M. sabahna sp. nov. The following synonymies are proposed: Myrmarachne topali Zabka, 1985 syn. nov. as a junior synonym of M. hanoii Zabka, 1985, M. gigantea Zabka, 1985 syn. nov. as a junior synonym of M. maxillosa (C. L. Koch, 1846). The females of M. assimilis Banks, 1930, M. biseratensis Badcock, 1918, M. gedongensis Badcock, 1918, M. markaha Barrion & Litsinger, 1995 and M. shelfordii Peckham & Peckham, 1907 are described for the first time